KEDUDUKAN AKTA KETERANGAN HAK MEWARIS DENGAN OBJEK WARISAN HAK ATAS TANAH ATAU HAK MILIK ATAS SATUAN RUMAH SUSUN YANG BERADA DI LUAR WILAYAH JABATAN NOTARIS - Giffari Yahya Muhamad; Suparjo (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
This paper written to analyze the consequence of the new provision in Minister of Agrarian and spatial planning/Head of National Land Agency regulation number 16 in 2021 which changes chapter 111. The new provision stipulate that the deed of inheritance rights should be made by a notary located at the inheritor domicile when they died. Based on the new provision, if the inheritance are land rights or ownership rights to the apartment units, the Notary who has the authority to made the deed of inheritance rights is the one who domiciled in the Inheritor Domicile not the one who domiciled where the lands are located. This research is conducted to find out if there are any legal problem because of the new provisions.